Probabilistic load flow based voltage stability assessment of solar power integration into power grids - Rehiara, Adelhard Beni; Bawan, Elias Kondorura; Palintin, Antonius Duma; Wihyawari, Bibiana Rosalina; Setiawan Paisey, Fourys Yudo; Pasalli, Yulianus Rombe (Institute of Advanced Engineering and Science, 2024)
The interconnection of renewable energies increases the complexity of modern power systems. Hence, stability assessments should be made to ensure the system’s stability after penetration. Solar power is a type of renewable energy that has become a widespread energy source among renewable energy sources. About 1 MWp of the solar power plant has been prepared to be interconnected to the IEEE 8 bus of Manokwari grid, and this paper investigates the voltage profile, power losses, and stability of the solar power plant penetration using an adaptive kernel density estimator (AKDE) and compares it to a Monte Carlo simulation (MCS)-based probabilistic load flow (PLF). About 5000 samples have been used to test the grid after the connection. Results of simulations show that the solar penetration can reduce power losses from 0.4084 MW to 0.3080 MW and 0.3045 MW by the proposed method and MCS method, respectively, and further increase the bus voltage profile. The power network has the stability to be connected to solar power, as indicated by the small stability index values of each bus. The proposed method using the AKDE method has a more accurate result in stability indices indicated by small fast voltage stability index (FVSI), line stability index (Lmn), and line stability factor (LQP) indices.